Pengelolaan Zakat, Infak, dan Sedekah dalam Perspektif Maqasid Syariah: Studi Kasus LAZDA RIZKI Jember - Ginanjar Permana, Eka; Usman, Musyafi (Kartika: Jurnal Studi Keislaman, 2025)
Indonesia, with a population of 284.4 million as of March 2024, continues to face poverty challenges, with 25.22 million people (9.03%) living below the poverty line. Zakat, Infak, and Sedekah (ZIS) possess substantial potential as instruments for poverty alleviation and socio-economic empowerment, yet their implementation remains suboptimal. This study aims to analyze the management of ZIS, covering collection, distribution, and utilization, examine strategies for improving community welfare, and assess their alignment with the principles of Maqasid al-Shariah as formulated by Imam al-Syatibi. Employing a descriptive qualitative method with sociological and normative approaches, the research draws on primary data obtained through interviews and observations at LAZDA RIZKI Jember, complemented by secondary data from institutional documents and relevant literature. The findings reveal that the ZIS management at LAZDA RIZKI, including innovative programs such as the Creative Empowerment Center (Balai Kreatif), systematically reflects the realization of the five core objectives of Maqasid al-Shariah: protection of religion, life, intellect, progeny, and wealth. This study contributes to the discourse on ZIS governance from a Maqasid-based perspective and offers practical insights for zakat institutions in optimizing their role in advancing social welfare.